Analisis Sistem Pemerintah Desa Di Indonesia - Ira Sandika; Syarifa Aini; Yona Kristin Simbolon; Sri Hadiningrum (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Village Government as a government entity at the local level has an important role in community development and empowerment. This research aims to conduct an in-depth analysis of the village government system in Indonesia with a focus on the organizational structure, policies and challenges faced. This study uses a qualitative descriptive research method by collecting data through interviews, observation and study of related documents. The results of the analysis show that the Village government system in Indonesia has various components, including the Village head, Village Consultative Body (BPD), and other Village officials. However, there are still several challenges that affect the effectiveness and efficiency of Village government. Factors such as limited resources, lack of access to information, and regulatory complexity are the main obstacles in carrying out the duties of the Village government. In addition, community involvement and the role of women in village decision making still need to be improved to ensure fair representation. This research also highlights the importance of improving central government policies related to Village funds and increasing human resource capacity at the Village level. Recommendations for improvement involve a holistic approach involving relevant parties, including the central government, regional government and local communities.